From Technology Transfer to Intercultural Development Understanding Technology and Development in a Globalising World - van der Stoep, Jan; Strijbos, Sytse (UJ Press, 2012)
The central theme of this book is the intercultural development of technology in a globalising world. Migration, tourism, information and communication technology and international trade stimulate tfhe encounter between cultures, leading to a totally new social configuration on a worldwide scale.